Infratentorial Posterior Reversible Encephalopathy Syndrome (PRES) Presenting with Hydrocephalus - C, Whitehead; R, Reehal; S, Shumon (Archives of Clinical and Medical Case Reports, 2019)
Posterior reversible leukoencephalopathy syndrome (PRES) is a cranial disorder linked to hypertension usually presenting with symptoms of headache, nausea and vomiting, seizures and visual disturbance. We present a rare case of PRES jointly managed by neurology and neurosurgery with an EVD and antihypertensive therapy in a 46 year old female who presented with hydrocephalus at Newcastle Upon Tyne Hospitals. Cases of PRES presenting in this way were rare with only 8 cases being described in the past. These cases tend to be in a much younger patient subset who were more often male. Management has varied in the past described cases and more literature is required to reach a concensus.